1991
DOI: 10.1007/bf01464296
|View full text |Cite
|
Sign up to set email alerts
|

The stability of hydrous oxide films on platinum

Abstract: The stability of hydrous oxide films grown on platinum in both acid and base was investigated as a function of holding potential in solutions of different pH. In contrast to similar films grown on gold -whose behaviour was described earlier -the stability of the bulk of the hydrous oxide deposks on platinum was not very dependent on solution pH. This was attributed to a rather facile rearrangement, in the case of platinum, of the initially anionic oxide species to a virtually neutral state. However, there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The first and second sweep of the cyclic voltammograms shown in Figure were recorded from 0.68 to −0.25 V at 10 mV s –1 on FTO. The onset of cathodic current at approximately ∼0.50 V and subsequent reduction peak (P1) at 0.059 V was attributed to the reduction of H 2 [Pt(OH) 6 ] to Pt [reaction ], in agreement with the reduction peak for the [Pt(OH) 6 ] 2‑ /Pt 0 redox couple in acidic media. …”
Section: Resultssupporting
confidence: 58%
“…The first and second sweep of the cyclic voltammograms shown in Figure were recorded from 0.68 to −0.25 V at 10 mV s –1 on FTO. The onset of cathodic current at approximately ∼0.50 V and subsequent reduction peak (P1) at 0.059 V was attributed to the reduction of H 2 [Pt(OH) 6 ] to Pt [reaction ], in agreement with the reduction peak for the [Pt(OH) 6 ] 2‑ /Pt 0 redox couple in acidic media. …”
Section: Resultssupporting
confidence: 58%
“…In the work of Birss et al [37], the formation of an oxide layer of PtO(OH) 2 with Pt(OH) 3 HSO 4 was reported after polarization at high anodic potentials in a 0.5 M sulfuric acid solution. Burke and coworkers also showed that platinum oxide films were formed with different compositions after anodic polarization at high potential [40,41]. As such two different forms of platinum oxides are likely observed here.…”
Section: Resultssupporting
confidence: 59%
“…Thus, hydrogen gas evolution on platinum in acid is a clear case where chemisorption of the intermediate is important; platinum hydrous oxide at low pH is quite unstable at low potentials (37) and is therefore not involved in this process. Thus, hydrogen gas evolution on platinum in acid is a clear case where chemisorption of the intermediate is important; platinum hydrous oxide at low pH is quite unstable at low potentials (37) and is therefore not involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the different mechanisms of electrocatalysis, both approaches appear to be valid. Thus, hydrogen gas evolution on platinum in acid is a clear case where chemisorption of the intermediate is important; platinum hydrous oxide at low pH is quite unstable at low potentials (37) and is therefore not involved in this process. However, oxidation of various solution species, e.g., DMAB (25), formaldehyde (6), and hydrazine (7), on gold (a very poor chemisorber) in base seems to be a clear case where the incipient hydrous oxide approach is valid; the different onset potentials for oxidation of these compounds correlates quite well with premonolayer oxidation processes reported (6) for this electrode system.…”
Section: __l Lmentioning
confidence: 99%